Difficulties in Management of Functional Movement Disorders: Three Illustrative Cases. Issue 6 (26th June 2021) - Nadler, Martine; Cary, Isabel; Symeon, Christopher
ABSTRACT: Background: Some patients with FND and FEVD cannot re‐establish walking ability with standard treatment alone. Cases: Novel invasive treatment of FEVD trialed in three females, aged 19, 30 and 33 years with >18 month history of FND. None could walk and all were wheelchair‐dependent needing home carers. Standard treatment plus novel step‐wise escalation of invasive "intervention+" was individually tailored to correct FEVD; functional electrical stimulation, botulinum toxin injections, tibial nerve block, serial casting, and for Case 3, manipulation under anesthetic and surgical tendon lengthening. All regained walking ability and discontinued carers. Case 1 resumed dancing and Case 3 returned to employment. Improvements were largely maintained at 3 and 6 month follow‐up. Conclusions: As a last resort, invasive adjuncts may be considered in a very small proportion of FND patients who fail to regain walking ability with standard treatment alone and reach a "dead end" where no further progress is feasible.